2018
DOI: 10.15436/2475-6245.18.1833
|View full text |Cite
|
Sign up to set email alerts
|

Survey the Prevalence of Pediculosis Capitis and its Associated Risk Factors among Girls’ Schools Students in Garmsar City, Semnan Province (Iran)

Abstract: Objective: The prevalence of head lice (Pediculus humanus capitis) is one of the prevalent infections in all ages particularly among students and has a worldwide distribution. Aim of this study was to survey the prevalence of head lice infestation and external factors affecting the distribution of P. capitis among girls' schools in Garmsar city and in the east of Semnan province (Iran) from December 2015 to March 2016. Methods: This was a descriptive and analytic study. A total of 800 students aged 7-16 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is well known that head lice is transmitted directly from person to person and crowded families are mostly at risk for pediculosis. The infestation ratio of pediculosis according to father education was 8.28% for educated father stufents and non-educated farther students was 10.82% and show that students with educated father are less infested than those who have non educated father, otherwise another study done in Garmsar City, Semnan Province, Iran shows that student with educated father are more infested than those have non educated father [29]. Also in a recent study carridout in northwest Ethiopia [30] have same result, while the our result have agreed with a study done in Turkey which indicated the student have an educated father are less infested compare to others that have non educated father this is may be due to the awearness of the fathers about the pediculosis and also the educated fathr and mother expected to hav a good personal hygene and health care knowledges.…”
Section: Prevalence Of Head Pediculosis Among Primary Aged School Childrenmentioning
confidence: 87%
“…It is well known that head lice is transmitted directly from person to person and crowded families are mostly at risk for pediculosis. The infestation ratio of pediculosis according to father education was 8.28% for educated father stufents and non-educated farther students was 10.82% and show that students with educated father are less infested than those who have non educated father, otherwise another study done in Garmsar City, Semnan Province, Iran shows that student with educated father are more infested than those have non educated father [29]. Also in a recent study carridout in northwest Ethiopia [30] have same result, while the our result have agreed with a study done in Turkey which indicated the student have an educated father are less infested compare to others that have non educated father this is may be due to the awearness of the fathers about the pediculosis and also the educated fathr and mother expected to hav a good personal hygene and health care knowledges.…”
Section: Prevalence Of Head Pediculosis Among Primary Aged School Childrenmentioning
confidence: 87%